CONCEPTION OF INFORMATIZATION OF PHARMACEUTICAL MARKET AND PHARMACEUTICAL SERVICES - Babintseva, L. Yu. (Medical Informatics and Engineering, 2012)
The article is devoted to development of conceptual fundamentals of increased effectiveness for managing a pharmaceutical market and pharmaceutical services due to the processes of informatization taking into account principles of integration in an only computer internetwork. The value of new information technologies is well-proven for the effective use of pharmaceutical information.